Factores sociodemográficos y actitud hacia la vacunación contra la COVID-19 en pobladores del asentamiento humano Iván Vásquez Valera Iquitos 2022 - Saavedra Carey, Ray Cristhoper (2024)
The objective was to determine the relationship between sociodemographic factors and attitude towards vaccination against COVID-19, in inhabitants of the Iván Vásquez Valera Human Settlement, Iquitos. It is a quantitative, non experimental, descriptive, cross-sectional and correlational study; whose sample was 116 inhabitants. The survey and the home visit were used as techniques; a questionnaire on sociodemographic factors (Validity 88.75%) and an attitudinal scale of vaccination against COVID-19 (validity 87.50% and reliability 81.12%). The results were: 64.7% adults and 35.3% youth; 72.4% women and 27.6% men; 50.0% with secondary education, 36.2% primary and 13.8% technical/higher; 51.7% housewives; 28.4% are self-employed, 8.6% are students, 6.9% are public employees and 4.3% are construction workers; 56.9% Catholics and 43.1% Evangelicals/other religions; 44.0% came from peri-urban Xelig, 41.4% rural and 14.7% urban. Regarding attitude, 82.8% showed acceptance and 17.2% rejection. Significance was found in age (p=0.036), Xeligión education (p=0.045) and Xeligión (p=0.030) with attitude; while with sex (p=0.415), occupation (p=0.649) and origin (p=0.610) no statistical significance was found in the inhabitants of Iván Vásquez Valera. Concluding that the adult inhabitants were the ones who acted positively, showing acceptance of the anticovid-19 vaccine, in favor of their health.